(untitled) (Journal of actual problems of jurisprudence, 2018)
The article analyzes the problem of administrative responsibility as one of the most versatile and most fully realized kinds of legal liability. The main approaches to the modern theory of administrative law for the definition of administrative responsibility. The main result of the study is to validate the fact that to determine the administrative responsibility as an independent type of legal liability is advisable to use a methodological approach, justifying the necessity of presence of basic criteria: industry criterion of differentiation of legal responsibility, a special mechanism for the implementation of responsibility, as well as the specific type of jurisdictional process, in which the type of liability is realized. Key words: responsibility, legal responsibility, administrative responsibility, the criterion base classification.